Evaluation of clinical and laboratory results of patients diagnosed urinary calculi in emergency department (Annals of Medical Research, 2023)
Aim: In this study, we examined the factors affecting the rate of urine culture positivity and the rate of urine culture positivity in patients who were found to have kidney stones in the emergency department and were followed up by the Urology outpatient clinic. We evaluated the examinations and treatments of these patients with the results of the urology outpatient clinic until the urine culture results were obtained. We think that our study will provide useful information to emergency service workers in the evaluation of patients with urinary system stones.Materials and Methods: In this study, patients who applied to Emergency Medicine Department of İnönü University Faculty of Medicine between January 1st, 2016 and November 1st, 2022, who were diagnosed with urinary calculi by imaging and who were followed up in the Urology outpatient clinic, were retrospectively analyzed. The age and gender of the patients, as laboratory tests, complete blood count, urinalysis, serology and urine culture results were examined. Multiple logistic regression analysis was performed with all the parameters obtained from our study and the analysis was statistically significant according to the Hosmer&Lemeshow test.Results: In our study, there were a total of 349 patients, 99 (28.37%) female and 250 (71.63%) male, and a pathogenic microorganism growth was observed in the urine culture of 40 (11.7%) of the patients. The first two microorganisms most frequently encountered in urine culture were Escherichia Coli (24/40) and Klebsiella spp. (5/40). In the logistic regression model, nitrite positivity increased 48.8%, urinary white blood cells increased 0.2%, bacteria presence in urine 3.06%, and increased patient age increased the probability of culture positivity by 2.6%. Each 1 unit increase in hemoglobin value decreased the probability of positive urine culture by 27.8%.Conclusion: The leukocyte count, bacteria presence, nitrite positivity, low blood hemoglobin and advancing advanced age in the complete expulsion examination of a patient with urinary system stone are the prediction of a positive ejection result. These data should be considered in the decision to take the culture of dissemination at the time of death of patients with urinary tract stones or the management of care during the time until they reach the respiratory tract.